ANALISIS PENDAPATAN PRODUK OLAHAN BAKSO IKAN MARLIN (Istiompax indica) DI UMKM DUHA FOOD - Quran, Farhatunnida Hamalatul; Nurhayati, Atikah; Iskandar, Iskandar; Maulina, Ine (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
This research aims to analyze the income of marlin fish meatballs at Duha Food MSMEs. The research was carried out in December 2023-July 2024. This research was carried out at the Duha Food UMKM located in Kp. Talun Kiarapayung RT/RW 04/09, Citepus Village, Palabuhanratu District, Sukabumi Regency, West Java Province. This research was carried out using a survey method and a sampling technique using purposive sampling. The research results were analyzed quantitatively descriptively. The data sources used are primary and secondary data. Primary data was obtained from filling out questionnaires and interviewing business owners. Secondary data was obtained from the Ministry of Maritime Affairs and Fisheries, the Central Statistics Agency, as well as literature studies related to this research. Data was analyzed descriptively quantitatively by analyzing income including fixed costs, variable costs, total costs, revenues. The research results show that the profit generated from processing marlin fish meatballs is IDR. 228,706,000 in one year.